Breakthrough in yam breeding - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1995)
Before the prolonged civil war in Sudan and drought in Ethiopia, farmers in those countries were planting white yams (Dioscorea rotundata). But now yam has almost completely disappeared from these countries because the planting portion of the crop...